Impact of Strategic, Tactical, Internal Green Marketing Orientation on Sustainability Performance -A Mediation Mechanism of Stakeholders’ Engagement - Nayab Mufti; Sajid, Muhammad; ul Ain, Qural; Abrar, Rabia (Journal of Applied Research and Multidisciplinary Studies, 2024)
The purpose of this paper is to examine the impact of strategic, tactical, and internal green marketing orientation on sustainability performance in textile small and medium size enterprises (SMEs) using concepts of Green Marketing Theory and Natural Resource-Based Theory. This study investigated the mediation mechanism of stakeholder engagement between three independent dimensions of green marketing orientations and sustainability performance. The quantitative survey methodology is used to collect data from managers of textile SMEs through purposive and snowball sampling technique. The proposed conceptual model and hypotheses are empirically tested using partial least squares structural equation modeling (PLS-SEM) technique in SmartPLS software. The study intends to make key theoretical contributions by extending green marketing orientation literature to incorporate strategic, tactical and internal dimensions and testing their relative effects on sustainability outcomes in emerging economies, particularly within the context of textile SMEs that are major contributor to environmental pollution. This study is aligned with the United Nations’ Sustainable Development Goal (SDG) 12 & 13, which aim to lessen the impact of climate change and increase ecological footprint through responsible production and consumption for the betterment of future. Moreover, this study also considers stakeholder engagement as an important variable in mediating these orientations and its impact on sustainability performance at economic, social and environmental objectives. The findings aim to advance the GMO theory by extending the scope for further academic/market validation and concurrently advancing managerial inferences for business strategists and market practitioners on sustainable organizational performance.